Exploring Caregiver Behavior and Knowledge About Unsafe Sleep Surfaces in Infant Injury Death Cases. (June 2015) - Chu, Tracy; Hackett, Martine; Kaur, Navpreet
Objectives. In the United States, infant deaths due to sleep-related injuries have quadrupled over the past two decades. One of the major risk factors is the placement of an infant to sleep on a surface other than a crib or bassinet. This study examines contextual circumstances and knowledge and behaviors that may contribute to the placement of infants on an unsafe sleep surface in infant injury death cases. Method. This study employed a retrospective review of 255 sleep-related injury death cases in New York City from 2004 to 2010 where an infant was found sleeping on an unsafe sleep surface. Mixed-methods analyses, employing both quantitative analysis of vital statistics data and risk variables extracted from the medical examiner files and qualitative analysis of the narrative content of the files, were conducted. Results. In 48% of cases, a crib or bassinet was identified in the home. Quantitative analysis revealed no significant differences in demographic or risk factor characteristics between infants who had a crib or bassinet and those who did not. Qualitative analysis highlighted factors in caregivers' decision making related to situational convenience, preference, and misconceptions concerning safe infant sleep. The health belief model (HBM), specifically the constructs of perceived susceptibility, severity, benefits, and barriers, was used as a lens to understand factors associated with caregiver behavior. Conclusions. This study provides evidence that infants are at risk of sleep-related injury death even when a crib or bassinet is present. Understanding the factors that may influence safe sleep behaviors can help produce more appropriate interventions.